The Influence of Career Women’s Rejection of Polygamy on Children’s Personality (Case Studi in Batu Aji District, Batam City) - Muhammad Nurul Fahmi; Nada Izzatun Nisa (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2023)
The appointment of this title is because the situation is experienced by the majority of people in Indonesia, especially in Batu Aji District, Batam. Starting from the number of divorce cases in Batam that were carried out by wives against their husband in 2022, there were finally 1.505 cases. Meanwhile, only 541 cases of divorce were filed by husbands. The polygamy solution that is prescribed by religion actually creates internal problems in the famil. What applies is that wives prefer to file for divorce and work alone to meet household needs and educate children at home rather than having to carry out the Shari’a. It is this dual role of a housewife as well as a breadwinner that ultimately impacts one the personality of the children at home. Starting in terms of psychology, morals, emotions and even education. The aims of this study were: (1) to analyze and discover the phenomenon of resistence to polygamy by career women in Batu Aji District, Batam, and (2) to analyze and find the impact of resistance to polygamy on the personality of children at home. This study uses a quamtitative approach with a case study type. The object of this research is the people of Batu Aji, Batam City. Data collection techniques are by survey questionnaires, interviews and observation.The result of this study indicate that, (1) the rejection of polygamy does not occor because it does not agree with the shari’a, there is a wrong implementation of polygamy and there are five factors of rejected polygamy, and (2) the thougest challenge in balancing a career and taking care of children is time and there are four effects of refusing polygamy on children. Keywords: rejection of polygamy; career woman; child personality.